Effectiveness of Ethno-STEM-Based Science Teaching with the Project-Based Learning Model on Students' Scientific Literacy - Imron, Erlambang Muhammad; Asri Nugraheni, Febriani Sarwendah; Utami, Budi; Nursalsabila, Zamzami; Mahardiani, Lina; Bramastia; Tanghal, Analiza B. (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
The results of the OECD in 2019 showed that in 2012-2018, the acquisition of scientific literacy in Indonesia was still relatively low compared to other countries. The pretest results also showed that the average value of students' scientific literacy was 65 out of 100. Learning based on empowering thinking skills and using the context frequently encountered by students can help students relate scientific knowledge to everyday life, particularly in the aspect of interpreting data and evidence scientifically. From these problems, the study aims to (1) reveal the effect of ethno-STEM-based science teaching based on drums on vibration and wave material on the scientific literacy of junior high school students, and (2) identify the scientific literacy profile of junior high school students in Surakarta based on measurements using scientific literacy question instruments on vibration and wave material. This study was quasi-experimental. The population was all eighth-grade students from three junior high schools in Surakarta, totaling 864 students. The sample consisted of two classes from each school, selected as experimental classes and six control classes, determined using a cluster random sampling method. Data was collected using a science literacy test. The results showed: (1) there was an effect of the ethno-STEM approach with the PJBL learning model on students' scientific literacy in junior high school science learning on vibrations and waves, tested using the ANCVA test with a significance level of 0.047, and (2) in the experimental classes at junior high schools A, B, and C, there was an increase in all aspects of scientific literacy. In the control class, the highest increase was observed in the aspect of evaluating scientific investigations, while the lowest increase was noted in the aspect of explaining phenomena scientifically